PENGARUH PEMBERIAN TUGAS BERBASIS PROYEK TERHADAP PENGEMBANGAN LIFE SKILL DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP - Warda Murti (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
Learning in school tended to focus on teacher until recently. Teacher's jobs is to deliver the subject materials and students learn to memorize all of the knowledge. learning which oriented on the Mastery of the material is only successful in in a short term memorization but fail to solve problems in future time. Project-based learning is used in order to make students active in learning and make teachers as facilitators. Moreover, the implementation of project-based learning will develop students’ life skills.This study aims at examining the influence of project-based task towards life skill development and learning achievement of grade VIII students in Junior high school (SMP). This study is a quasi experimental, that two samples were given a treatment using different learning methods and observe the influence toward life skill development and students’ learning achievement. The design used was Posttest Only Control Group Design with 37 students as the samples for the control groupn and 37 students as well as the experiment group. Data were collected using observation sheet to measure the life skill, multiple choice test to measure the result of cognitive learning of students. Data were analyzed descriptively and inferentially (t-test statistics with SPSS 17.0 program for Windows, conducted with the level of significant 5%).The results of study reveal that (1) the project-based task gives influence toward life skill development of grade VIII students and (2) project-based task gives influence toward learning achievement the outcome of Biology of grade VIII students.